CITIZENS' PERSONAL DATA, AND ITS' CLASSIFICATION IN CURRENT DOCTRINE OF ADMINISTRATIVE LAW - Цьоменко, А. (Київський національний університет імені Тараса Шевченка, 2023)
The paper is dedicated to issues on determination of citizens' personal data, and classification of its in current doctrine of Administrative Law. There is stressed, the search of the model of legal mechanism of relationships of personal data protection regulation has place in the domestic legal science. This model should agree with international legal standards and guarantee an effective protection of human and citizen rights and freedoms. As a result, it has to become a part of implementation of the national legal system in European legal field. There is outlined, the administrative and legal provisions of relationship on personal data circulating and processing provides an effect on relationship of legal means with administrative and legal features. An analysis of doctrinal definitions demonstrates a versatility of the definition of personal data. The social and legal nature is reflected in it. There is identified, personal data is any information in objective form which provides possibility to determine its information source, and related to a subject of data. The subject of personal data is an identified or such who can be identified natural person (citizen), in relation to whose public authorities and other authorized subjects are endowed with subjective obligation of providing appropriative level of organizational and legal safety and protection. There is emphasized, citizen personal data have such signs as: informational content i.e., on the point of view of majority scientists, personal data are information or set of information (including any information) about a person; identifying feature; fixed form and reflection in specific source (data carriers); inexhaustibility; acquire the legal regime of personal data when personal data processing starts i.e., any action or set of such actions as collection, registration, accumulation, saving, adaptation, changing, renovation, use and spread (distribution, implementation, transfer), depersonalization, utilization, including use of information (automatized) systems. Taking into account the analysis of legal nature of personal data on the point of view of the Administrative Law, doctrinal approaches, and international and legal regulation, we can suggest to separate personal data into the following groups, using criteria of their content and level of established "availability". These groups are: general (or publicly available), special, and biometrical. At the same time, biometrical personal data include genetical data about a person, and data related to the health or medical data of citizens.

Присвячено питанням визначення персональних даних громадян та їх класифікації у сучасній доктрині адміністративного права. Наголошено, що у вітчизняній юридичній науці триває пошук моделі правового механізму регулювання відносин із захисту персональних даних, яка узгоджувалася б з міжнародно-правовими стандартами, гарантувала б ефективний захист прав і свобод людини та громадянина, що має стати частиною імплементації національної правової системи у спільний європейський правовий простір. Зазначено, що адміністративно-правове забезпечення відносин обігу та обробки персональних даних полягає у впливі на такі відносини юридичних засобів адміністративно-правового характеру. Аналіз доктринальних визначень демонструє багатогранність визначення персональних даних, у чому і знаходить своє відображення їхня соціально-правова природа. Визначено, що персональні дані громадян – це будь-яка інформація в об'єктивізованій формі, що дає можливість визначити її інформаційне джерело, і стосується суб'єкта даних, тобто ідентифікованої або такої, що піддається ідентифікації фізичної особи (громадянина) та відносно якої органи публічної влади й інші уповноважені суб'єкти наділені суб'єктивним обов'язком забезпечення належного рівні організаційно-правової охорони та захисту. Наголошено, що персональним даним громадян властиві такі ознаки, як: інформаційний зміст, тобто персональні дані, з точки зору більшості науковців, виступають як відомості чи сукупність відомостей (включає будь-яку інформацію) про особу; ідентифікуюча властивість; фіксована форма та відображення в певному джерелі (носії даних); невичерпність; набувають правового режиму персональних даних із початком обробки, тобто будь-якої дії або сукупності дій таких, як: збирання, реєстрація, накопичення, зберігання, адаптування, зміна, поновлення, використання і поширення (розповсюдження, реалізація, передача), знеособлення, знищення персональних даних, у тому числі з використанням інформаційних (автоматизованих) систем. Відштовхуючись від аналізу правової природи персональних даних з позиції галузі адміністративного права, доктринальних підходів і міжнародно-правового регламентування, наведено підхід щодо виділення їх видів. Запропоновано розділити персональні дані громадян на групи, використовуючи критерії їхнього змістового наповнення та рівня встановленої "доступності": загальні (або загальнодоступні), спеціальні та біометричні. Водночас різновидами біометричних персональних даних громадян виступають генетичні дані про особу та дані, що стосуються здоров'я, або медичні персональні дані громадян.
ПЕРСОНАЛЬНІ ДАНІ ГРОМАДЯН ТА ЇХНЯ КЛАСИФІКАЦІЯ В СУЧАСНІЙ ДОКТРИНІ АДМІНІСТРАТИВНОГО ПРАВА
Keywords: Administrative Law; personal data; providing of citizens' personal data protection; authorities; classification; types of personal data; адміністративне право; персональні дані; забезпечення захисту персональних даних громадян; органи влади; класифікація; види персональних даних